A preparation method of cesium acetate cooperated with nitrogen-doped lignin porous carbon material

CN122035858BActive Publication Date: 2026-10-09YANBIAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610143925.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-02
Publication Date
2026-10-09
Estimated Expiration
2046-02-02

AI Technical Summary

Technical Problem

但未经改性的木质素三维网状结构稳定,直接碳化后孔隙结构不发达、比表面积小,电化学性能不佳;且传统改性过程中化学试剂的使用易引发二次污染

Benefits of technology

[0014] The present invention discloses a method for preparing cesium acetate-co-nitrogen-doped lignin porous carbon materials, which is resource-sustainable and environmentally friendly: using agricultural waste sodium lignin sulfonate as a carbon source, the resource utilization of waste is realized, reducing raw material costs; cesium acetate serves as a template agent and activator, eliminating the need for dangerous reagents such as hydrofluoric acid to remove the template, and subsequent washing with dilute hydrochloric acid is sufficient, simplifying wastewater treatment and avoiding secondary pollution; the activation temperature during the preparation process is relatively low (cesium acetate activation can be started at ≈600℃, and the final carbonization temperature is 800℃, lower than the >800℃ required for K/Na compound activation), resulting in lower energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122035858B_ABST
    Figure CN122035858B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a cesium acetate synergistic nitrogen-doped lignin porous carbon material, and comprises the following steps: step S1: 10g of NH3H2O, 20g of sodium lignosulfonate and 20g of H2O2 are sequentially added into 160mL of deionized water, and stirring is carried out for 1h until uniform mixing is achieved; after cooling to room temperature, the mixture is poured into a round-bottom flask, and vacuum concentration is carried out through a rotary evaporator to obtain a thickened liquid; after drying of the concentrated product in a blast oven, grinding is carried out to obtain a lignin intermediate which is low in molecular weight and rich in oxygen-containing and nitrogen-containing functional groups. The application relates to the technical field of supercapacitor electrode materials, and has the beneficial effects of resource sustainability and environmental protection: the agricultural waste sodium lignosulfonate is used as a carbon source, so that the waste is utilized as a resource, and the cost of raw materials is reduced; the cesium acetate is used as a template agent and an activator, so that dangerous reagents such as hydrofluoric acid are not needed to remove the template, and only dilute hydrochloric acid needs to be used for subsequent washing; wastewater treatment is simple, and secondary pollution is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of supercapacitor electrode materials, and in particular to a method for preparing cesium acetate-co-nitrogen-doped lignin porous carbon materials. Background Technology

[0002] With the rapid development of the new energy industry, supercapacitors have become a research hotspot due to their high energy storage and fast charge / discharge characteristics. Their performance is primarily dependent on electrode materials. Currently, supercapacitor electrode materials are mainly classified into double-layer type and pseudocapacitive type. Double-layer type relies on ion adsorption-desorption for energy storage, offering high power density but limited energy density; pseudocapacitive type stores energy through Faraday reaction, achieving higher energy density but lacking sufficient cycle stability and rate performance.

[0003] Most existing electrode materials are derived from non-renewable coal or fossil petroleum, which are not only scarce resources but also pose an environmental burden. Lignin, as a natural organic compound found in agricultural waste, has advantages such as low cost, wide availability, high carbon content, and good thermal stability, making it an ideal renewable carbon source. However, the stable three-dimensional network structure of unmodified lignin results in an underdeveloped pore structure and small specific surface area after direct carbonization, leading to poor electrochemical performance. Furthermore, the use of chemical reagents in traditional modification processes can easily cause secondary pollution.

[0004] Template-based methods are a common technique for preparing porous carbon materials. Pore structures can be constructed through the spatial occupancy of template agents. However, additional activators are required to improve the electrochemical performance of the materials, leading to complex and inefficient preparation processes. For example, in the existing dual-template method (MgO / F127) for preparing lignin-based porous carbon, subsequent activation with KOH is necessary to improve specific capacitance. While some template agents (such as NaCl and NaNO3) can achieve a certain specific surface area, their specific capacitance performance is poor, still requiring additional activation. Furthermore, traditional activators (such as KOH and Na2CO3) require high temperatures (>800℃) to function, resulting in high energy consumption and stringent equipment requirements.

[0005] Therefore, developing a preparation system that can simultaneously possess template and activation functions, is environmentally friendly, and has low energy consumption, and further optimizing the electrochemical performance of lignin-based porous carbon through effective modification methods, has become a pressing technical challenge in the field of supercapacitor electrode materials. Summary of the Invention

[0006] The purpose of this invention is to solve the above-mentioned problems by designing a method for preparing cesium acetate-co-nitrogen-doped lignin porous carbon materials.

[0007] The technical solution of the present invention to achieve the above objectives is a method for preparing cesium acetate-co-nitrogen doped lignin porous carbon materials, comprising the following steps:

[0008] Step S1: Add 10g NH3・H2O, 20g sodium lignosulfonate and 20g H2O2 to 160mL deionized water in sequence and stir for 1h until uniformly mixed; after cooling to room temperature, pour into a round-bottom flask and concentrate under vacuum using a rotary evaporator to obtain a thickened liquid; dry the concentrated product in a forced-air oven and grind it to obtain a low molecular weight lignin intermediate rich in oxygen- and nitrogen-containing functional groups;

[0009] Step S2: The pretreated lignin intermediate was mixed and ground with cesium acetate at mass ratios of 1:1, 1:2, 1:3, 1:4, and 1:6, and then spread evenly in a ceramic boat. The ceramic boat was placed in a tube furnace and heated to 800℃ at a heating rate of 5℃ / min, and held at that temperature for 2 hours for carbonization. After grinding, the carbonized product was washed with 1M HCl, then washed with deionized water to remove impurities and residual HCl, and finally dried overnight in an 80℃ forced-air drying oven to obtain a series of porous carbon materials, named LCC-1, LCC-2, LCC-3, LCC-4, and LCC-6, respectively. To verify the dual function of cesium acetate as a template agent and activator in improving the structure and performance of lignin-based porous carbon materials, a control experiment without cesium acetate was set up to eliminate the interference of the carbonization effect of lignin itself. The lignin directly carbonized without cesium acetate was used as the control sample (LC) to clarify the key role of cesium acetate in pore formation, activation, and electrochemical performance optimization.

[0010] Step S3: Pretreated lignin and cesium acetate were mixed and ground at a mass ratio of 1:1, spread evenly in a ceramic boat, and carbonized in a tube furnace; the carbonized product was mixed and ground with urea at mass ratios of 1:0.5, 1:1, 1:2, and 1:3, spread evenly in a ceramic boat, and heated to 400℃ at a heating rate of 2℃ / min, and held at that temperature for 2 hours for secondary carbonization and nitrogen doping diffusion; the product was washed with 1M HCl and deionized water, and then dried at 80℃ overnight to obtain a series of nitrogen-doped porous carbon materials LCNC-0.5, LCNC-1, LCNCs-2, and LCNC-3; to clarify the template of cesium acetate- To investigate the synergistic effect of activation and nitrogen doping, it is necessary to exclude the influence of urea doping alone on the performance of lignin-based carbon materials. By setting up a control experiment with only urea doping, and using pretreated lignin and urea directly mixed and carbonized (mass ratio 1:1) as the control sample (LNC), the key role of cesium acetate combined with nitrogen doping in optimizing pore structure and improving electrochemical performance can be accurately verified.

[0011] Step S4: Mix carbon material, SuperP, and PVDF at a mass ratio of 8:1:1, add an appropriate amount of NMP, and grind until a uniform slurry is formed; coat the slurry onto a 1cm × 1cm carbon cloth and dry it in a vacuum oven at 60℃ for 12 hours. The specific capacitance is calculated based on the constant current charge-discharge (GCD) curve, and the calculation formula is as follows: The carbon material loading (1-2 mg) needs to be calculated. Electrochemical performance testing of the derived carbon electrode was conducted: a three-electrode setup was used, with 6 M KOH as the electrolyte, platinum as the counter electrode, and Hg / HgO as the reference electrode.

[0012] In step S1, the purity of 10g NH3・H2O is 25-28%, the purity of 20g H2O2 is 30%, and the temperature of vacuum concentration in the rotary evaporator is 60℃.

[0013] In step S3, the carbonization temperature of the tubular furnace is increased to 800℃ at a rate of 5℃ / min and held for 2 hours.

[0014] The present invention discloses a method for preparing cesium acetate-co-nitrogen-doped lignin porous carbon materials, which is resource-sustainable and environmentally friendly: using agricultural waste sodium lignin sulfonate as a carbon source, the resource utilization of waste is realized, reducing raw material costs; cesium acetate serves as a template agent and activator, eliminating the need for dangerous reagents such as hydrofluoric acid to remove the template, and subsequent washing with dilute hydrochloric acid is sufficient, simplifying wastewater treatment and avoiding secondary pollution; the activation temperature during the preparation process is relatively low (cesium acetate activation can be started at ≈600℃, and the final carbonization temperature is 800℃, lower than the >800℃ required for K / Na compound activation), resulting in lower energy consumption.

[0015] High preparation efficiency: Cesium acetate has the dual functions of template agent and activator, eliminating the need for additional activators, simplifying the preparation process and improving production efficiency; after lignin is pretreated with ammonia water and hydrogen peroxide, its three-dimensional network structure is broken, and it is transformed into a highly reactive intermediate. It works synergistically with cesium acetate, resulting in a carbon yield of up to 40%, which meets the needs of large-scale production.

[0016] Excellent pore structure: Through the "cesium effect" (cesium ions are large in size, have weak binding force with anions, and have a strong effect on the distortion of carbon networks), combined with the pore-forming effect in the pyrolysis of cesium acetate, the prepared LCC-3 material has a specific surface area of ​​up to 3047 m² / g and a pore volume of 2.83 cm³ / g. The hierarchical porous structure, which is mainly composed of micropores and contains a small amount of mesopores, is conducive to ion adsorption and rapid transfer.

[0017] Excellent electrochemical performance: In a three-electrode system, LCC-3 has a specific capacitance of up to 396 F / g at a current density of 0.5 A / g, and still maintains 264 F / g at 20 A / g. After 5000 cycles at 10 A / g, the capacitance retention rate is 88.8%, which balances high specific capacitance, high rate performance and long cycle stability. The nitrogen-doped LCNC-1 has a further increased specific surface area of ​​3168.22 m² / g and a specific capacitance of 278 F / g at 0.5 A / g, which is a significant improvement over the undoped LCC-1 (219.5 F / g), achieving synergistic enhancement of double-layer capacitance and pseudocapacitance.

[0018] Compared with existing porous carbon materials prepared by SiO2 templates and NaCl / NaNO3 templates, the material of this invention has significant advantages in specific surface area, pore volume, specific capacitance and environmental friendliness of preparation (e.g., the specific capacitance of SiO2 template material is only 156.8 F / g, and NaCl template requires additional KOH activation). Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the LCC electrode material preparation process of the cesium acetate synergistic nitrogen-doped lignin porous carbon material preparation method described in this invention.

[0020] Figure 2 These are scanning electron microscope (SEM) images of LCC porous carbon with different cesium acetate ratios in the preparation method of cesium acetate synergistic nitrogen doped lignin porous carbon material according to the present invention: (a) lignin carbon material without added cesium acetate (LC); (b) LCC-1; (c) LCC-2; (d) LCC-3; (e) LCC-4; (f) LCC-6.

[0021] Figure 3 These are LC-X scanning electron microscope (SEM) images of porous carbon prepared using different salt templates according to the method for preparing cesium acetate-co-nitrogen-doped lignin porous carbon materials described in this invention: (a) LCC-3 prepared using a cesium acetate template; (b) LC-CsCc prepared using a cesium carbonate template; (c) LC-KCc prepared using a potassium carbonate template; (d) LC-KAc prepared using a potassium acetate template; (e) LC-NaCc prepared using a sodium carbonate template; and (f) LC-NaAc prepared using a sodium acetate template.

[0022] Figure 4 This is a verification of the preparation method of cesium acetate-co-nitrogen-doped lignin porous carbon material according to the present invention. LCC-3 has a high specific surface area (3047 m² / g), large pore volume (2.83 cm³ / g), and hierarchical pore structure dominated by micropores. Among them, (a) nitrogen adsorption-desorption curve of lignin carbon material (LC) without cesium acetate addition; (b) nitrogen adsorption-desorption curve and pore size distribution of LCC-3; (c) X-ray diffraction (XRD) analysis diagrams of LC, LCC-2, LCC-3 and LCC-4; (d) Raman spectra of LCC-2, LCC-3 and LCC-4.

[0023] Figure 5The images are scanning electron microscope (SEM) images of nitrogen-doped porous carbon in proportion to the method for preparing cesium acetate synergistic nitrogen-doped lignin porous carbon material according to the present invention: (a) LNC with only urea nitrogen doping; (b) LCNC-0.5 with a lignin to urea mass ratio of 1:0.5; (c) LCNC-1 with a lignin to urea mass ratio of 1:1; (d) LCNC-2 with a lignin to urea mass ratio of 1:2.

[0024] Figure 6 This document verifies the preparation method of a cesium acetate-co-nitrogen-doped lignin porous carbon material as described in this invention. LCNC-1 exhibits an ultra-high specific surface area (3168.22 m² / g) and a pure pore structure dominated by micropores. Images include: (a) nitrogen adsorption-desorption curve of LNC doped only with urea nitrogen; (b) nitrogen adsorption-desorption curve and pore size distribution of LCNC-0.5; (c) nitrogen adsorption-desorption curve and pore size distribution of LCNC-1; (d) X-ray diffraction (XRD) analysis of LCNC-0.5, LCNC-1, and LCNC-2; and (e) Raman spectra of LCNC-0.5, LCNC-1, and LCNC-2.

[0025] Figure 7 This invention confirms the successful doping of nitrogen into the cesium acetate-co-nitrogen-doped lignin porous carbon material, demonstrating the successful doping of nitrogen into the material. It clarifies the elemental composition, chemical state, and functional group types (e.g., C=C, CN, NH) of the material. The images include: (a) X-ray photoelectron spectroscopy (XPS) full spectra of LC, LCNC-1, and LCNC-0.5; (b) statistical graph of nitrogen content in each material; and the X-ray photoelectron spectroscopy (XPS) peak fitting diagram of the AOL-N-Cs-1 carbon material: (c) C1s orbital; (d) O1s orbital; (e) N1s orbital; and (f) Fourier transform infrared (FTIR) spectra of LC, LCNC-0.5, and LCNC-1.

[0026] Figure 8 This is a visual demonstration of the preparation method of cesium acetate-co-nitrogen-doped lignin porous carbon material according to the present invention. LCC-3 has the longest charge-discharge time, the largest CV curve area, the highest specific capacitance (396 F / g), and excellent cycling stability (88.8% retention rate after 5000 cycles). Among them, (a) is a comparison of galvanostatic charge-discharge (GCD) curves of porous carbon electrode materials with different cesium acetate ratios at a current density of 0.5 Ag⁻¹; (b) is a comparison of cyclic voltammetry (CV) curves of porous carbon electrode materials with different cesium acetate ratios at a scan rate of 5 mVs⁻¹; (c) is the specific capacitance value of porous carbon electrode materials with different cesium acetate ratios at different current densities; (d) is the cycling stability curve of LCC-3 at a current density of 10 Ag⁻¹.

[0027] Figure 9 These are electrochemical test images of electrode materials prepared with different salt templates in a three-electrode system according to the method for preparing cesium acetate-co-nitrogen-doped lignin porous carbon materials described in this invention: (a) Cyclic voltammetry (CV) curve at a scan rate of 5 mVs⁻¹; (b) Galvanostatic charge-discharge (GCD) curve at a current density of 0.5 Ag⁻¹.

[0028] Figure 10 This is a demonstration of the preparation method of cesium acetate synergistic nitrogen-doped lignin porous carbon material according to the present invention. LCNC-1 has the largest CV curve area, the longest charge-discharge time and a high specific capacitance (278F / g), verifying the effect of nitrogen doping on improving electrochemical performance. Among them, (a) is a comparison of cyclic voltammetry (CV) curves of porous carbon electrode materials with different urea doping ratios at a scan rate of 5mVs⁻¹; (b) is a comparison of galvanostatic charge-discharge (GCD) curves of porous carbon electrode materials with different urea doping ratios at a current density of 0.5Ag⁻¹; (c) is the specific capacitance value of porous carbon electrode materials with different urea doping ratios at different current densities; (d) is the cycle stability curve of LCNC-1 at a current density of 10Ag⁻¹. Detailed Implementation

[0029] The present invention will now be described in detail with reference to the accompanying drawings, such as... Figure 1-10 As shown, a method for preparing cesium acetate-co-nitrogen-doped lignin porous carbon material involves sequentially adding 10g of NH3·H2O (purity 25-28%), 20g of sodium lignin sulfonate, and 20g of H2O2 (purity 30%) to 160mL of deionized water and stirring for 1h until uniformly mixed. After cooling to room temperature, the mixture is poured into a round-bottom flask and concentrated under vacuum (60℃) using a rotary evaporator to obtain a thickened liquid. The concentrated product is then dried in a forced-air oven and ground to obtain a low-molecular-weight lignin intermediate rich in oxygen- and nitrogen-containing functional groups.

[0030] The pretreated lignin intermediate was mixed and ground with cesium acetate at mass ratios of 1:1, 1:2, 1:3, 1:4, and 1:6, and then spread evenly in a ceramic boat. The ceramic boat was placed in a tube furnace and heated to 800°C at a rate of 5°C / min, and held at that temperature for 2 hours for carbonization. The carbonized product was ground, washed with 1M HCl, and then washed with deionized water to remove impurities and residual HCl. Finally, it was dried overnight in an 80°C forced-air drying oven to obtain a series of porous carbon materials, named LCC-1, LCC-2, LCC-3, LCC-4, and LCC-6, respectively. Lignin that was directly carbonized without the addition of cesium acetate was used as a control sample (LC).

[0031] To verify the advantages of cesium acetate, potassium acetate, sodium acetate, cesium carbonate, potassium carbonate, and sodium carbonate were selected as template agents. The preparation method of LCC-3 (template agent to lignin mass ratio 1:3) was followed, and the remaining steps remained unchanged to prepare comparative samples LC-KAc, LC-NaAc, LC-CsCc, LC-KCc, and LC-NaCc.

[0032] Pretreated lignin was mixed and ground with cesium acetate at a mass ratio of 1:1, spread evenly in a ceramic boat, and carbonized in a tube furnace (heated to 800℃ at a rate of 5℃ / min and held for 2 hours). The carbonized product was mixed and ground with urea at mass ratios of 1:0.5, 1:1, 1:2, and 1:3, spread evenly in a ceramic boat, heated to 400℃ at a rate of 2℃ / min, and held for 2 hours for secondary carbonization and nitrogen doping diffusion. The product was washed with 1M HCl and deionized water, and then dried at 80℃ overnight to obtain a series of nitrogen-doped porous carbon materials LCNC-0.5, LCNC-1, LCNCs-2, and LCNC-3. Pretreated lignin was directly mixed with urea and carbonized (mass ratio of 1:1) as a control sample (LNC).

[0033] Carbon material, SuperP, and PVDF were mixed in a mass ratio of 8:1:1, and an appropriate amount of NMP was added and ground until a uniform slurry was formed. The slurry was coated onto a 1cm×1cm carbon cloth and dried in a vacuum oven at 60℃ for 12 hours. The carbon material loading was calculated (1-2mg).

[0034] A three-electrode system was formed using a platinum sheet as the counter electrode, mercury / mercuric oxide as the reference electrode, and 6MKOH as the electrolyte. Cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and impedance (EIS) tests were performed.

[0035] The features of this implementation scheme are as follows: lignin pretreatment: ammonia water provides an alkaline environment, hydrogen peroxide is used as an oxidant, the mixing ratio of the three is NH3・H2O: sodium lignin sulfonate: H2O2 = 10g: 20g: 20g, the amount of deionized water is 160mL, the stirring time is 1h, the concentration temperature is 60℃, and the product is thoroughly ground after drying.

[0036] LCC preparation: The optimal mass ratio of pretreated lignin to cesium acetate is 1:3 (corresponding to LCC-3), the carbonization heating rate is 5℃ / min, the carbonization temperature is 800℃, the holding time is 2h, the washing is done with 1MHCl, and the drying temperature is 80℃.

[0037] LCNC preparation: The mass ratio of pretreated lignin to cesium acetate was 1:1, and the carbonization parameters were the same as those for LCC preparation; the optimal mass ratio of carbonization product to urea was 1:1 (corresponding to LCNC-1), the secondary carbonization heating rate was 2℃ / min, the temperature was 400℃, and the holding time was 2h.

[0038] Electrode preparation: The mass ratio of carbon material, SuperP, and PVDF is 8:1:1. The amount of NMP used is based on the standard that the slurry is "thick but not dry, thin but not dripping". The carbon cloth size is 1cm×1cm. The drying temperature is 60℃ and the drying time is 12h. The carbon material loading is controlled at 1-2mg.

[0039] Preferred material properties:

[0040] 1. LCC-3: Specific surface area 3047m² / g, pore volume 2.83cm³ / g, specific capacitance 396F / g at 0.5A / g, specific capacitance 264F / g at 20A / g, capacitance retention rate 88.8% after 5000 cycles at 10A / g, suitable for supercapacitors with high requirements for power density and cycle stability.

[0041] LCNC-1: Specific surface area 3168.22m² / g, pore volume 1.67cm³ / g, specific capacitance 278F / g at 0.5A / g, specific capacitance 208F / g at 20A / g, capacitance retention rate 78.1% after 5000 cycles at 10A / g, suitable for supercapacitors with higher energy density requirements.

[0042] In this implementation plan, 1. Carbon source replacement: Sodium lignin sulfonate can be replaced with other agricultural waste-derived lignin (such as straw lignin, bagasse lignin), or industrial lignin by-products, to further expand the sources of raw materials and reduce costs.

[0043] 2. Heteroatom doping improvement: In addition to urea as a nitrogen source, melamine, ammonia, pyridine, etc. can be used as nitrogen sources, or other heteroatoms such as phosphorus and sulfur can be introduced for co-doping to further regulate the functional groups and electrochemical properties of the material surface.

[0044] 3. Template agent optimization: Cesium acetate can be combined with other low-toxicity template agents (such as biological templates and polymer templates) to further optimize the pore structure distribution and balance the specific surface area and conductivity.

[0045] 4. Improved preparation process: New processes such as microwave carbonization and plasma activation can be used to replace traditional tube furnace carbonization, shortening the preparation time and reducing energy consumption; or porous carbon materials with specific morphologies (such as fibrous or spherical) can be prepared by spray drying, electrospinning and other technologies to improve electrode forming performance.

[0046] 5. Electrolyte compatibility: The electrolyte can be replaced from 6MKOH aqueous solution with organic electrolyte or ionic liquid electrolyte, expanding the voltage window of the material and further improving the energy density of the supercapacitor.

[0047] In this implementation plan, such as Figure 1The content shown clearly presents the complete process of lignin pretreatment, mixing with cesium acetate, carbonization, washing and drying to obtain LCC series porous carbon materials. Key raw materials (NH3・H2O, sodium lignin sulfonate, H2O2, cesium acetate), core process parameters (carbonization temperature 800℃, heating rate 5℃ / min, holding time 2h), intermediate products and final products are marked.

[0048] The illustration serves to visually reflect the preparation logic of the electrode material of this invention and to clarify the connection between each step and the key conditions.

[0049] like Figure 2 The content shown includes 6 sub-images, namely (a) SEM images of LC (cesium acetate-free control sample), (b) LCC-1 (mass ratio 1:1), (c) LCC-2 (mass ratio 1:2), (d) LCC-3 (mass ratio 1:3), (e) LCC-4 (mass ratio 1:4), and (f) LCC-6 (mass ratio 1:6), with scale bars of 5μm or 10μm.

[0050] The illustration serves to show the effect of different cesium acetate ratios on the material morphology. It can be seen that LCC-3 exhibits a distinct honeycomb structure with the most abundant pores, verifying its optimal ratio characteristics.

[0051] like Figure 3 The content shown includes 6 sub-images, namely (a) SEM images of LC (cesium acetate-free control sample), (b) LCC-1 (mass ratio 1:1), (c) LCC-2 (mass ratio 1:2), (d) LCC-3 (mass ratio 1:3), (e) LCC-4 (mass ratio 1:4), and (f) LCC-6 (mass ratio 1:6), with scale bars of 5μm or 10μm.

[0052] The illustration serves to show the effect of different cesium acetate ratios on the material morphology. It can be seen that LCC-3 exhibits a distinct honeycomb structure with the most abundant pores, verifying its optimal ratio characteristics.

[0053] like Figure 4 The content shown includes four sub-figures: (a) is the nitrogen adsorption-desorption curve of LC, (b) is the nitrogen adsorption-desorption curve and pore size distribution of LCC-3, (c) is the XRD pattern of LC, LCC-2, LCC-3 and LCC-4, and (d) is the Raman spectrum of LCC-2, LCC-3 and LCC-4.

[0054] The illustration serves to verify that LCC-3 possesses a high specific surface area (3047 m² / g), large pore volume (2.83 cm³ / g), and a hierarchical pore structure dominated by micropores, while also reflecting the crystal structure and degree of disorder of the material.

[0055] like Figure 5The content shown includes 6 sub-images, namely (a) SEM images of LNC (control sample without cesium acetate doping), (b) LCNC-0.5 (urea mass ratio 1:0.5), (c) LCNC-1 (urea mass ratio 1:1), (d) LCNC-2 (urea mass ratio 1:2), (e) LCNC-3 (urea mass ratio 1:3), and (f) LCC-1 (control sample without nitrogen doping), with scale bars of 5 μm or 10 μm.

[0056] The illustration illustrates the effect of nitrogen doping ratio and cesium acetate on the material morphology. It shows that LCNC-1 has abundant pores and a dense layered structure, which is beneficial for ion transport and structural stability.

[0057] like Figure 6 The content shown includes 5 sub-figures: (a) nitrogen adsorption-desorption curve of LNC, (b) nitrogen adsorption-desorption curve and pore size distribution of LCNC-0.5, (c) nitrogen adsorption-desorption curve and pore size distribution of LCNC-1, (d) XRD patterns of LCNC-0.5, LCNC-1 and LCNC-2, and (e) Raman spectra of the three.

[0058] The illustration serves to verify that LCNC-1 possesses an ultra-high specific surface area (3168.22 m² / g) and a pure pore structure dominated by micropores, while also reflecting the influence of nitrogen doping on the crystal structure and disorder of the material.

[0059] like Figure 7 The content shown includes 6 sub-figures: (a) is the XPS full spectrum of the three, (b) is the nitrogen content bar chart, (c), (d) and (e) are the high-resolution XPS fitting plots of C1s, O1s and N1s of LCNC-1, respectively, and (f) is the FTIR spectrum of the three.

[0060] The purpose of the illustration is to confirm that nitrogen has been successfully incorporated into the material, and to clarify the elemental composition, chemical state, and functional group type (such as C=C, CN, NH) of the material.

[0061] like Figure 8 The content shown includes four sub-figures: (a) a comparison of GCD curves at a current density of 0.5 A / g; (b) a comparison of CV curves at a scan rate of 5 mV / s; (c) a bar chart of specific capacitance at different current densities; and (d) a cycle stability curve of LCC-3 at 10 A / g.

[0062] The illustration serves to visually demonstrate that LCC-3 has the longest charge-discharge time, the largest CV curve area, the highest specific capacitance (396F / g), and excellent cycle stability (88.8% retention rate after 5000 cycles).

[0063] The illustration contains two sub-figures: (a) a comparison of CV curves at a scan rate of 5 mV / s, and (b) a comparison of GCD curves at a current density of 0.5 A / g.

[0064] like Figure 9 The content shown is: comparing the electrochemical performance of materials prepared with different salt templates, highlighting that the cesium acetate template (LCC-3) has the largest CV curve area, the longest charge-discharge time, and the best specific capacitance (396F / g).

[0065] like Figure 10 The content shown includes four sub-figures: (a) a comparison of CV curves at a scan rate of 5mV / s, (b) a comparison of GCD curves at a current density of 0.5A / g, (c) a bar chart of specific capacitance at different current densities, and (d) a cycle stability curve of LCNC-1 at 10A / g.

[0066] The illustration serves to demonstrate that LCNC-1 has the largest CV curve area, the longest charge-discharge time, and a relatively high specific capacitance (278 F / g), verifying the effect of nitrogen doping on improving electrochemical performance.

[0067] In this implementation scheme, renewable sodium lignosulfonate is used as the carbon source, and cesium acetate is innovatively selected as both a template agent and an activator. By adjusting the ratio of the two, a porous carbon material with high specific surface area and optimized pore structure is constructed. Furthermore, nitrogen doping modification is introduced, and pseudocapacitance is introduced by the Faraday reaction of nitrogen-containing functional groups to synergistically improve the specific capacitance and cycle stability of the material, ultimately obtaining a high-performance supercapacitor electrode material.

[0068] The above technical solutions only embody the preferred technical solutions of the present invention. Any modifications that may be made by those skilled in the art to certain parts thereof embody the principles of the present invention and fall within the protection scope of the present invention.

Claims

1. A method for preparing a cesium acetate-co-nitrogen-doped lignin porous carbon material, characterized in that, Includes the following steps: Step S1: Add 10g NH3・H2O, 20g sodium lignosulfonate and 20g H2O2 to 160mL deionized water in sequence and stir for 1h until uniformly mixed; after cooling to room temperature, pour into a round-bottom flask and concentrate under vacuum using a rotary evaporator to obtain a thickened liquid; dry the concentrated product in a forced-air oven and grind it to obtain a low molecular weight lignin intermediate rich in oxygen- and nitrogen-containing functional groups; Step S2: Mix and grind the pretreated lignin and cesium acetate at a mass ratio of 1:1, spread them evenly in a porcelain boat, and carbonize them in a tube furnace. The carbonization temperature in the tube furnace is increased to 800℃ at a rate of 5℃ / min and held for 2 hours. The carbonization product was mixed and ground with urea at mass ratios of 1:0.5, 1:1, 1:2, and 1:3, and spread evenly in a ceramic boat. The temperature was increased to 400℃ at a rate of 2℃ / min and held for 2 hours for secondary carbonization and nitrogen doping diffusion. The product was washed with 1M HCl and deionized water, and then dried at 80℃ overnight to obtain a series of nitrogen-doped porous carbon materials LCNC-0.5, LCNC-1, LCNCs-2, and LCNC-3. Step S3: Mix carbon material, SuperP and PVDF in a mass ratio of 8:1:1, add an appropriate amount of NMP and grind until a uniform slurry is formed; coat the slurry onto a 1cm×1cm carbon cloth and dry it in a vacuum oven at 60℃ for 12 hours.

2. The method for preparing cesium acetate-co-nitrogen doped lignin porous carbon material according to claim 1, characterized in that, In step S1, the purity of 10g NH3・H2O is 25-28%, the purity of 20g H2O2 is 30%, and the temperature of vacuum concentration in the rotary evaporator is 60℃.

Citation Information

Patent Citations

  • Pre-activated-carbonized lignin-based hard carbon as well as preparation method and application thereof

    CN120736520A